2015
DOI: 10.1371/journal.pone.0116375
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Levels of 25-Hydroxyvitamin D and Functional Outcome among Postmenopausal Women with Hip Fracture

Abstract: ObjectiveThe main objective of the current study was to assess the distribution and its prognostic value of serum 25-hydroxyvitamin D (25[OH] D) levels assessed at admission in Chinese postmenopausal women with hip fracture.MethodsFrom January 1, 2012 to December 31, 2013, all postmenopausal women with first-ever hip fracture were recruited to participate in the study. Serum 25[OH] D levels were measured at admission. The functional evaluation at the time of discharge was performed by the Barthel Index (BI). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Many authors reported on the connection between fracture risk and VD deficiency [ 1 , 3 , 6 , 26 ]. Nevertheless, there is few data on the relation between VD status, postoperative healing [ 9 , 14 , 15 , 16 , 17 ] and survival [ 2 , 4 , 7 , 8 ]. All these studies focused on the t-25OHD levels without binding proteins and the outcome after surgery without considering lifestyle and MCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors reported on the connection between fracture risk and VD deficiency [ 1 , 3 , 6 , 26 ]. Nevertheless, there is few data on the relation between VD status, postoperative healing [ 9 , 14 , 15 , 16 , 17 ] and survival [ 2 , 4 , 7 , 8 ]. All these studies focused on the t-25OHD levels without binding proteins and the outcome after surgery without considering lifestyle and MCD.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 17 ] reported similar results, but their threshold limit was higher (29.5 nmol/L) than ours (22.6 nmol/L). According to Liu et al [ 14 ], 76 patients with an unfavorable functional outcome had lower serum t-25OHD levels, compared to those with better functional performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van et al [ 28 ] reported that a serum level of 25(OH) D <30 nmol/L was associated with an increased risk of fractures in the youngest, but not in the oldest, age group after adjustment for confounders. Interestingly, Liu et al [ 29 ] found that there was an association between serum 25(OH) D levels and prognosis in Chinese postmenopausal women with hip fracture. Differences in the assay and sample test methods, subject populations, and analytic platforms used may explain the inconsistencies among studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 72.3 % of subjects with hip fracture had vitamin D levels less than 50 nmol/L, and 63.6 % had hyperparathyroidism. Similarly, in another Chinese sample, almost four-fifths of the hip fracture patients (78.9 %) had vitamin D deficiency [ 29 ].…”
Section: Discussionmentioning
confidence: 99%